Embracing Complexity: Ambidextrous Leadership Enriching Job Satisfaction in Nepalese Commercial Banking Sector - Chalise, Dhan Raj; Paudel , Vishal (PT FORMOSA CENDEKIA GLOBAL, 2024)
Scholars argue that ambidexterity serves as a crucial precursor not only to organizational innovation but also for teams and individual workers. This study indulges into ambidexterity and analyzes the synergic combination of transformational and transactional leadership style to create ambidextrous leadership and the positive impact of ambidextrous leadership on job satisfaction in Nepalese commercial banks. The research employed a survey design to collect data from 150 employees in Nepali commercial banks. Simple random sampling techniques were utilized, and a questionnaire was administered to gauge respondents' job satisfaction levels with various dimensions of transactional leadership styles, employing a five-point Likert scale. The findings reveal a significant relationship between ambidextrous leadership style dimensions and job satisfaction in Nepali commercial banks. The study concludes that ambidextrous leadership is the potential to be the most influential leadership style for fostering job satisfaction and recommends the balancing of counteracting leadership styles promoting ambidextrous leadership in Nepali commercial banks